A new active power filter topology based on a chopper circuit - 郭晓玲 程健 张波 张旌 黄远 (Chinese physics C, 2016)
Active power filters （APFs） are widely used for their outstanding performance in current and voltage rip- ple compensation. As modern high-energy accelerators are demanding much more stringent current ripple guidelines, APFs are used in the magnet power supply （MPS） in accelerator systems. However, conventional APFs have many drawbacks due to the traditional topology, such as complex structure, nonadjustable working voltage, requirement of power supply, and so on. This paper proposes a new APF topology, which works as two types of chopper circuits. This APF does not need extra electricity, but uses the power of the MPS current ripple to realize ripple depression. Experimental results prove its feasibility and effectiveness.